2013
DOI: 10.1007/s00134-012-2798-3
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic stone protein as a novel marker for neonatal sepsis

Abstract: Background: Most clinical trials of sepsis treatment modalities fail at their primary objective of establishing superiority over placebo when added to background standard of care. While there is no definitive explanation for the high failure rate, it might be stated that our attempts to insert a new therapeutic agent into standard of care encounters severe problems with definition of exactly what stage is ongoing, and what are the criteria for progression or resolution from that time point onwards. Clearly the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 33 publications
6
42
1
Order By: Relevance
“…This is consistent with existing studies on healthy neonates [14, 29]. It is important that in future studies on EOS the diagnostic value of age-adjusted PCT cut-offs will be assessed in association with other serum biomarkers [46, 53]. …”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with existing studies on healthy neonates [14, 29]. It is important that in future studies on EOS the diagnostic value of age-adjusted PCT cut-offs will be assessed in association with other serum biomarkers [46, 53]. …”
Section: Discussionsupporting
confidence: 87%
“…In humans, MIF is present in the amniotic fluid and is expressed in the fetal membranes of the placenta and in the fetal and neonatal lungs (2831). Interestingly, circulating levels of MIF are at least 10-fold higher in healthy term newborns than in adults (30, 32, 33). We recently reported that high expression levels of MIF sustain innate immune responses of newborn monocytes and counter-regulate the activity of adenosine and prostaglandin E2, two immunosuppressive mediators produced at high levels by the placenta (33).…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic stone protein (PSP) belongs to the family of lectin-binding proteins, and is constitutively secreted by pancreatic acinar cells into pancreatic juice along with zymogens. PSP is a relatively novel marker and research related to it is sparse [26,27]. Palmiere et al reported that PSP and PCT were positively correlated with mortality in patients with or without sepsis, and that the PSP levels were distinctly higher than in sepsis [28].…”
Section: Discussionmentioning
confidence: 99%
“…Peng et al observed a significant positive correlation between PSP and WBC, as well as serum PCT levels [7]. Schlapbach et al also used combined testing of PSP and PCT to diagnose early-onset sepsis [27]. The levels of PSP were closely related to the degree of infection.…”
Section: Discussionmentioning
confidence: 99%